Effect of Some Amino Acids on the Structure and Activity of Carbonic Anhydrase - Sarraf, N.S.; A. Saboury, A.; Ranjbar, B.; Nemat-Gorgani, M. (Asian Journal of Chemistry, 2016)
The effect of three amino acids, histidine, phenylalanine and aspartic acid, as three different osmolytes, on the structure and activity of bovine carbonic anhydrase has been studied using different techniques. All the three amino acids were found to stabilize the enzyme against inactivation alongside of time. While the thermal transition temperature was the same as control in all cases, DGº25, a quantitative marker for thermal stability was found to be affected differently by the three amino acids. Besides, it seems that in the presence of phenylalanine, as a hydrophobic osmolyte, the structure of the enzyme is somehow exposed while aspartic acid, as a negatively charged amino acid, may induce the contraction of the protein. Histidine can make carbonic anhydrase get some extra secondary structure while the tertiary structure is not considerably changed. The in-vitro studies may make some points of view for future ex-vivo study on the effect of these osmolytes on the stability and activity of carbonic anhydrase.